Metabolic effects of eradicating breath methane using antibiotics in prediabetic subjects with obesity - Mathur, Ruchi; Chua, Kathleen S.; Mamelak, Mindy; Morales, Walter; Barlow, Gillian M.; Thomas, Rita; Stefanovski, Darko; Weitsman, Stacy; Marsh, Zachary; Bergman, Richard N.; Pimentel, Mark (Obesity (Silver Spring, Md.), 2016)
Objective Methanogens colonizing the human gut produce methane and influence host metabolism. This study examined metabolic parameters in methane‐producing subjects before and after antibiotic treatment. Methods Eleven prediabetic methane‐positive subjects (9F, 2M) with obesity (BMI 35.17 ± 7.71 kg/m2) aged 47 ± 9 years were recruited. Subjects underwent breath testing, symptom questionnaire, oral glucose tolerance test (OGTT), lipid profile, and stool Methanobrevibacter smithii levels, gastric transit, and energy utilization analyses. After a 10‐day antibiotic therapy (neomycin 500 mg bid/rifaximin 550 mg tid), all testing was repeated. Results Baseline stool M. smithii levels correlated with breath methane (R = 0.7, P = 0.05). Eight subjects (73%) eradicated breath methane and showed reduced stool M. smithii (P = 0.16). After therapy, methane‐eradicated subjects showed significant improvements in low‐density lipoprotein (LDL) (P = 0.028), total cholesterol (P = 0.01), and insulin levels on OGTT (P = 0.05 at 120 minutes), lower blood glucose levels on OGTT (P = 0.054 at 90 minutes), significant reductions in bloating (P = 0.018) and straining (P = 0.059), and a trend toward lower stool dry weight. No changes were detected in gastric emptying time or energy harvest. Conclusions Breath methane eradication and M. smithii reduction are associated with significant improvements in total cholesterol, LDL, and insulin levels and with lower glucose levels in prediabetic subjects with obesity. The underlying mechanisms require further elucidation.